The Influence of Motivation and Working Skills Toward Employee Performance at Social Department of Kaur Regency - Indah Laini; Siti Hanila; Yesi Indiana Riska (Journal of Indonesian Management, 2021)
The purpose of this research is to find out the influence of motivation and civil servant performance at Social Department of Kaur Regency. This research uses descriptive quantitative research method. Sample are taken by using census technique and obtain 45 civil servants and temporary workers at Social Department of Kaur Regency. Research are analyzed by using spearman rank correlation with z-test as hypothesis test. From the discussion of correlation between motivation and working performance at Social Department of Kaur regency. From the description above, there is a significance correlation between motivation with civil servants’s performance. It is proofed with rs/correlation coefficient score 0,0546 with medium interpretation criteria. While Zcount score is 3,63 higher than Ztable score 1,96 caused H0 is rejected and H1 is accepted means the research hypothesis is accepted. There is significance correlation between working performance with civil servant performance. It is proofed by rs/correlation coefficient score is 0,730 with strong interpretation criteria. While Zcount score (4,84) is higher than Ztable (1,96) means the hypothesis is accepted.